FERTILIZER APPLICATION ORGANIC LIQUID (LOF) NASA AND BIOCOMPOST ON THE GROWTH AND YIELD OF EDAMAME SOYBEAN PLANTS(Glycine max ( L.) Merr): APLIKASI PUPUK ORGANIK CAIR (POC) NASA DAN BIOKOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG KEDELAI EDAMAME (Glycine max (L.) Merr) - Elvrida Rosa; Bustami; Fadhil Alfarizi (ROCE : Jurnal Pertanian Terapan, 2026)
This research was conducted to evaluate the influence of NASA LOF and biocompost on the growth performance of edamame soybean (Glycine max (L.) Merr.). The experiment employed a 4×4 factorial Randomized Block Design, where the first factor consisted of four concentrations of NASA LOF (P0 = control, P1 = 5 ml/L per polybag, P2 = 10 ml/L per polybag, and P3 = 15 ml/L per polybag). In contrast, the second factor involved four levels of biocompost application (B0 = control, B1 = 50 g/polybag, B2 = 100 g/polybag, and B3 = 150 g/polybag). The results indicated that varying concentrations of NASA LOF (P1, P2, and P3) did not produce significant differences in plant height at 14 DAP, and no significant variation was observed among the LOF treatments. The greatest number of pods per plant was recorded in the control treatment (P0), which was statistically comparable to the P2 treatment. Similarly, the highest pod weight per plant was obtained under the control treatment and did not differ significantly from P2. Biocompost application significantly influenced plant height at 14 DAP; however, its effect was not significant at 28 and 42 days after planting for all dosage levels. The highest pod number was observed in the B3 treatment (150 g/polybag), although it was not statistically different from the B0, B1, and B2 treatments. In contrast, Pods weight per plant was not significantly affected by biocompost application at any dosage level.